2020
DOI: 10.1021/acs.jpcb.0c09496
|View full text |Cite
|
Sign up to set email alerts
|

Laurdan and Di-4-ANEPPDHQ Influence the Properties of Lipid Membranes: A Classical Molecular Dynamics and Fluorescence Study

Abstract: Environmentally sensitive (ES) dyes have been used for many decades to study the lipid order of cell membranes, as different lipid phases play a crucial role in a wide variety of cell processes. Yet, the understanding of how ES dyes behave, interact, and affect membranes at the atomistic scale is lacking, partially due to the lack of molecular dynamics (MD) models of these dyes. Here, we present ground-and excited-state MD models of commonly used ES dyes, Laurdan and di-4-ANEPPDHQ, and use MD simulations to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 75 publications
(106 reference statements)
0
19
0
Order By: Relevance
“…Experimental techniques, such as deuterium NMR, , can directly measure S CD . The fluorescence spectroscopy using the environment-sensitive probe Laurdan provides the generalized polarization (GP) parameter of the lipids (also called as Laurdan GP order), which measures the local ordering of the lipids around the probe. , It was observed that the Laurdan GP and the deuterium NMR order parameters are in a linear relationship with each other . The MD simulation can directly calculate S CD of the lipid.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental techniques, such as deuterium NMR, , can directly measure S CD . The fluorescence spectroscopy using the environment-sensitive probe Laurdan provides the generalized polarization (GP) parameter of the lipids (also called as Laurdan GP order), which measures the local ordering of the lipids around the probe. , It was observed that the Laurdan GP and the deuterium NMR order parameters are in a linear relationship with each other . The MD simulation can directly calculate S CD of the lipid.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent labels [514][515][516][517][518][519][520][521][522][523][524][525][526][527][528][529] Fragrance Musk xylene [132] 2-aminoethoxydiphenyl borate (inhibitor of IP 3 receptors and TRP channels) [530] Organic solvents…”
Section: Application Xenobioticmentioning
confidence: 99%
“…Fluorescence microscopy with environmentally sensitive probes Dyes change the composition of the bilayers and may alter properties (60). They also do not generally allow the environment around specific molecules to be probed as the dyes are usually untargeted.…”
Section: Methods Limitations Required Developmentsmentioning
confidence: 99%